The Masters of Physics: Critical Thinking Through Skateboarding - Robertson, William H. (Advances in Social Sciences Research Journal, 2019)
This paper focuses on the use of live action and video instruction as a method of content dissemination and to motivate students in learning in science, technology, engineering and mathematics (STEM) education. Specifically, this area, dubbed “edutainment”, chronicles different interactions with students, teachers and community members that utilized live action to video as methods of capturing relevant content in student-centered contexts. The fundamental idea is to infuse one’s passion into modern methods of teaching, and to inspire others to use their gifts in their education, and thereby connect them to their dreams and aspirations.